2000
DOI: 10.1016/s0960-9822(00)00652-7
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of EGF receptor signaling by a metastasis suppressor, the tetraspanin CD82/KAI-1

Abstract: The 'metastasis suppressor' CD82/KAI-1, a member of the tetraspanin superfamily of transmembrane proteins, is widely distributed in normal tissues [1], and has been shown to be suppressed in the advanced stages of various epithelial malignancies [2-6]. Although the physiological relevance of this change is unknown, in vitro data show that ectopically expressed CD82/KAI-1 can suppress tumor cell migration, a process underlying the dissemination of tumor cells in vivo [5]. The function of CD82/KAI-1 is not known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
180
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(189 citation statements)
references
References 19 publications
7
180
1
1
Order By: Relevance
“…c-Met, the receptor for HGF/SF, is known to regulate migration and invasion and has been implicated in promoting metastasis in many different kinds of cancers (Pisters et al, 1995;Birchmeier et al, 1997Birchmeier et al, , 2003Wang et al, 2001), including prostate cancer (Humphrey et al, 1995;Nishimura et al, 1998;Knudsen et al, 2002;van Leenders et al, 2002;Nakashiro et al, 2003;Knudsen and Edlund, 2004). Previous studies in a mammary tumor cell line demonstrated that CD82 expression attenuated EGF-mediated EGFR signaling and reduced migration (Odintsova et al, 2000). In PC3 or DU145 cells, we did not observe significant changes in integrin-induced activation of EGFR or EGFR levels due to CD82 expression (not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…c-Met, the receptor for HGF/SF, is known to regulate migration and invasion and has been implicated in promoting metastasis in many different kinds of cancers (Pisters et al, 1995;Birchmeier et al, 1997Birchmeier et al, , 2003Wang et al, 2001), including prostate cancer (Humphrey et al, 1995;Nishimura et al, 1998;Knudsen et al, 2002;van Leenders et al, 2002;Nakashiro et al, 2003;Knudsen and Edlund, 2004). Previous studies in a mammary tumor cell line demonstrated that CD82 expression attenuated EGF-mediated EGFR signaling and reduced migration (Odintsova et al, 2000). In PC3 or DU145 cells, we did not observe significant changes in integrin-induced activation of EGFR or EGFR levels due to CD82 expression (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…EGF-mediated signaling and wound closure were shown to be attenuated after ectopic expression of CD82 in a breast tumor cell line (Odintsova et al, 2000). Accelerated endocytosis of the EGFR-EGF complex was suggested to be the cause for signal attenuation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A most interesting molecule in this group was CD82 (also termed kangai 1, suppressor of tumourigenicity 6, KAI1), as it was the only molecule being upregulated after 6 h (factor, 2.3) and 18 h (factor, 2.2) of CXCL12a stimulation, respectively. The transmembrane protein CD82 is directly associated with the epidermal growth factor receptor (EGFR) and other tyrosine kinase receptors and accelerates desensitisation of tyrosine receptor induced signalling correlated with an increased rate of receptor endocytosis (Odintsova et al, 2000). This attenuation of EGFR signalling by CD82 explains for its recently identified role as metastasis suppressor gene for prostate and pancreatic cancer (Dong et al, 1995;Guo et al, 1996).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%